2016
DOI: 10.5005/jp-journals-10005-1362
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Shear Bond Strength of Various Glass Ionomer Cements to Dentin of Primary Teeth: Anin vitroStudy

Abstract: AimTo evaluate and compare shear bond strength of various glass ionomer cements (GICs) to dentin of primary teeth.Materials and methodsSample size taken for the study was 72 deciduous molars with intact buccal or lingual surfaces. Samples were randomly divided into three groups, i.e., groups A, B, and C and were restored with conventional type II GIC, type II light cure (LC) GIC, and type IX GIC respectively. Thermocycling was done to simulate oral conditions. After 24 hours, shear bond strength was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 91 publications
3
19
0
Order By: Relevance
“…Resin-modified glass ionomer cement (RMGIC), which is also considered as a self-adhesive material/cement, has been developed by adding resin components to GIC to overcome the problem of moisture sensitivity, and offers the benefit of both resins and GIC like fluoride release and greater strength (Kapoor, Prabhu, & Balakrishnan, 2017;Pathak, Shashibhushan, Poornima, & Reddy, 2016;Rosenstiel, Land, & Crispin, 1998). In RMGIC, the resin component was thought to act as a reinforcing agent, resulting in the combination of micromechanical interlocking and chemical adhesion (Sekhar, Anil, Thomas, & Ginjupalli, 2017;Somani, Jaidka, Singh, & Sibal, 2016). RelyX Luting used in the study is a resin-modified powder/liquid glass ionomer luting cement and the results showed there was an inverse relationship between shear bond strength and severity of fluorosis, except comparison between moderate and severe groups had no statistical significance, which was partially in accordance with Awliya and Akpata (1999).…”
Section: Discussionmentioning
confidence: 99%
“…Resin-modified glass ionomer cement (RMGIC), which is also considered as a self-adhesive material/cement, has been developed by adding resin components to GIC to overcome the problem of moisture sensitivity, and offers the benefit of both resins and GIC like fluoride release and greater strength (Kapoor, Prabhu, & Balakrishnan, 2017;Pathak, Shashibhushan, Poornima, & Reddy, 2016;Rosenstiel, Land, & Crispin, 1998). In RMGIC, the resin component was thought to act as a reinforcing agent, resulting in the combination of micromechanical interlocking and chemical adhesion (Sekhar, Anil, Thomas, & Ginjupalli, 2017;Somani, Jaidka, Singh, & Sibal, 2016). RelyX Luting used in the study is a resin-modified powder/liquid glass ionomer luting cement and the results showed there was an inverse relationship between shear bond strength and severity of fluorosis, except comparison between moderate and severe groups had no statistical significance, which was partially in accordance with Awliya and Akpata (1999).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of clinical success of any intra-oral restorative materials depends mainly upon sealing ability and good adhesion of such restoration with tooth structure, and its resistance to various dislodging forces acting within the oral cavity. These bonds are not only important between restoration and tooth structure to prevent microleakage and minimize pulp irritation, hypersensitivity, or secondary caries but also, between cement base and tooth to remain in its place under masticatory function or during the application overlying restorative material (3,37) .…”
Section: Discussionmentioning
confidence: 99%
“…Shear bond strength could be defined as, the resistance to forces that tend to slide restorative material past tooth structure. As the major dislodging forces at the tooth restoration interface are of shearing type, so this type of strength is of greater importance to be determined than any other types of intra oral stresses (3) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations